Perancangan dan Analisis Sistem Informasi Pelayanan Administrasi Kependudukan Sebagai Pengembangan E-government Di Kecamatan Krembung - Didit Kristianto (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
In implementing e-government-based government, good population management is needed in order to provide services for related parties and to produce better performance. Therefore, a software that is able to handle the management of occupation services properly is needed. The methods and tools used in this research are Structured System Analysis and Design (SSAD) method, document flowchart, Data Flow Diagrams (DFD), ERD, and program flowcharts. This system runs towards internet usage so that it can be accessed by Krembung District residents anywhere and anytime. This system is built using PHP programming language and MySQL database. With this e-government-based population information system, it is easier for residents and officers to process population data.